2015
DOI: 10.2174/2212798407666150616125550
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Modeling of Respiration Rate of Tomato (Cultivar Roma) for Modified Atmosphere Storage

Abstract: Experiments were conducted to determine the respiration rate of tomato at 10, 20 and 30 °C using closed respiration system. Oxygen depletion and carbon dioxide accumulation in the system containing tomato was monitored. Respiration rate was found to decrease with increasing CO2 and decreasing O2 concentration. Michaelis-Menten type model based on enzyme kinetics was evaluated using experimental data generated for predicting the respiration rate. The model parameters that obtained from the respiration rate at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The respiration rate of tomato was obtained through the closed respiration system experiments at 10°C. Kandasamy et al [21] reported detailed experiment as well as calculation procedures.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The respiration rate of tomato was obtained through the closed respiration system experiments at 10°C. Kandasamy et al [21] reported detailed experiment as well as calculation procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the respiration rate of tomato was considered mainly as a function of O 2 concentration. [21] The inhibition parameter K 3 , calculated as the rate of CO 2 evolution, was inversely related to temperature, whereas the one calculated as the rate of O 2 consumption was directly proportional to the temperature. This is because the rate of CO 2 evolution during the respiration process is not same as the rate of O 2 consumption.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations